2020
DOI: 10.1186/s40100-020-00158-0
|View full text |Cite
|
Sign up to set email alerts
|

Women in household decision-making and implications for dietary quality in Bhutan

Abstract: Despite the wide range of literature supporting the linkages between women's empowerment and food security, it is not examined in social contexts where females historically enjoy equality and even favoritism, for instance where there is female succession and/or polyandry. This study was done in the Kingdom of Bhutan where matrilineal succession and polyandry were prevalent during the twentieth century. Both quantitative and qualitative survey methods were employed with the objectives of (i) investigating women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…This study also found that mothers and fathers in some households are performing other ‘non‐traditional’ gender normative roles, such as mothers contributing to the provision of food/resources and fathers supporting the responsibilities of food preparation, child feeding and household chores, despite social disapproval. Mothers as economic contributors can lead to more equitable household gendered decision making (Kadiyala et al, 2014), more equitable intrahousehold food allocation (Harris‐Fry et al, 2017), improved availability of nutritious foods for young children (Harris‐Fry et al, 2020) and improved complementary feeding practices (Bezner Kerr, 2005, 2016; Chintalapudi et al, 2018; Kuche et al, 2020; Oddo & Ickes, 2018; Sariyev et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that mothers and fathers in some households are performing other ‘non‐traditional’ gender normative roles, such as mothers contributing to the provision of food/resources and fathers supporting the responsibilities of food preparation, child feeding and household chores, despite social disapproval. Mothers as economic contributors can lead to more equitable household gendered decision making (Kadiyala et al, 2014), more equitable intrahousehold food allocation (Harris‐Fry et al, 2017), improved availability of nutritious foods for young children (Harris‐Fry et al, 2020) and improved complementary feeding practices (Bezner Kerr, 2005, 2016; Chintalapudi et al, 2018; Kuche et al, 2020; Oddo & Ickes, 2018; Sariyev et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Women have played increasing roles in agriculture and natural resource management and are vital agents of climate change adaptations. However, this potential of women remained untapped and there is limitation of research to showcase the gaps (B€ athge 2010; Andrijevic et al 2020;Sariyev et al 2020). To achieve these roles of women, there should be enabling policies and institutions that are gender mainstreamed (Mishra et al 2012;Glemarec et al 2016;Holman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, this potential of women remained untapped and there is limitation of research to showcase the gaps ( Bäthge 2010 ; Andrijevic et al. 2020 ; Sariyev et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, women's educational attainment and employment position were found to be the most critical determinants of their empowerment and participation in decisionmaking in all aspects of household life. Other similar findings incorporated by Sariyev et al [20] in Bhutan showed that women did not lack considerable engagement in home decisionmaking; the assessments suggested that the relationship between women's participation in decision-making and dietary habits is non-linear. Furthermore, Awan et al [21] discovered that women's involvement in the formal and informal labor markets had attained significant national and worldwide significance.…”
Section: Introductionmentioning
confidence: 56%